Analisis Potensi Pajak Restoran Kabupaten Tegal di Tengah Pandemi Covid-19 - Amin, Mohammad Arridho Nur (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
Restaurant Tax is a type of local tax that has great revenue potential for the region, so in the implementation of its collection the tegal district government targets to achieve regional tax revenue. The purpose of this study is to determine the level of achievement of potential, effectiveness, and contribution of Restaurant Tax to the Original Income of Tegal Regency in the midst of the Covid-19 Pandemic. The research analysis method used is descriptive qualitative with primary data collection techniques in the form of interviews, observations, and documentation. Secondary data contains the amount of local tax revenue and Local Revenue to analyze the level of potential achievement, effectiveness, and tax contribution. The results of the study show that the tax potential of Tegal Regency in 2020 has decreased due to covid-19, this is due to the large number of people who are reluctant to leave the house both to buy food and recreation. The target given by the government in taxes could not be met due to the decline in restaurant turnover, so many restaurants are making efficiencies on their employees in order to survive in this declining economic condition.